The existence and the construction of ‘Ilm al-kalam as Islamic discipline and its significance to wasatiyyah - Siraj, Fuad Mahbub; Arif, Ridwan; Efendi, (Penerbit Universiti Kebangsaan Malaysia, 2020)
‘Ilm al-kalam or in short the kalam focuses on the fundamental aspects in Islam. This science is important, and it should be used as a guideline in conducting Islamic studies. Essentially, the kalam offers the metaphysical and theological realm, the transcendental domain and future direction; its openness and rational thinking characteristics are necessary and useful for humans; it is not a very rigid discipline of a theoretical science. We need the adamant efforts and the courage to rethink and reconstruct the heritage endowed to us by the scholars of kalam in the past. In other words, it is probably necessary to make a new "ijtihad" because after all the “ijtihad” of the scholars in the past is still considered until now as a good standard in the tradition of Islamic thought. The need for the new ijtihad is due to the new ideologies and approaches associated or linked with Islam and Islamic missionary plans, organizations and activities involving Muslims as well as non-Muslims in the 21st century.